Fortification systems of the bronze-age settlements in Istria – concepts and changes (Archaeologia Adriatica, 2020)
The paper presents the results of the systematic archaeological excavations of the defense system at Monkodonja Hillfort carried out between 1997 and 2008. Some characteristics of the construction and changes in it – particularly of the hill fort entrance – are compared with other Bronze-Age hillforts in Istria and Eastern Mediterranean. The paper proposes possible reasons for and datings of the changes in the rampart and gate construction that coincided with the appearance of new weapons and, consequently, with new methods of warfare.
Keywords: Bronze Age; Istria; Monkodonja; hillforts; fortifications; dating